2021
DOI: 10.1016/j.breast.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with loss to follow-up of breast cancer patients: A retrospective analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, in oncology, Endo et al [23] investigated the loss to follow-up during active surveillance in 425 patients with stage I seminoma and found that 14% of patients on active surveillance were lost to follow-up in the frst two years and 38% in the frst fve years. In breast cancer patients, Ouyang et al [24] reported a loss to follow-up rate of 12.9% (198/1536 patients) in the frst year and 26.8% (411/1536 patients) in the ffth year after surgery. Santiá et al [9] reported a similar loss to follow-up rate of 19% (37/194 patients) after the 6th year, which increased to 30% (97/326 patients) after the 16th year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in oncology, Endo et al [23] investigated the loss to follow-up during active surveillance in 425 patients with stage I seminoma and found that 14% of patients on active surveillance were lost to follow-up in the frst two years and 38% in the frst fve years. In breast cancer patients, Ouyang et al [24] reported a loss to follow-up rate of 12.9% (198/1536 patients) in the frst year and 26.8% (411/1536 patients) in the ffth year after surgery. Santiá et al [9] reported a similar loss to follow-up rate of 19% (37/194 patients) after the 6th year, which increased to 30% (97/326 patients) after the 16th year.…”
Section: Discussionmentioning
confidence: 99%
“…Santiá et al [9] reported a similar loss to follow-up rate of 19% (37/194 patients) after the 6th year, which increased to 30% (97/326 patients) after the 16th year. Possible countermeasures include the use of reminder intervention to improve adherence to appointments, such as postradiotherapy follow-up [9,[22][23][24][25]. In a cross-sectional study, Bruns et al [25] demonstrated that reminder intervention in breast cancer patients resulted in signifcantly higher rates of attendance at postradiotherapy follow-up; specifcally, he reported an absolute decrease in nonattendance from about 24% to 18% after written (postal) reminders and from about 24% to 9% after telephone reminders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our sample size is in line with previous publications [ 19 ], and considerably higher than other real-world studies [ 16 ]. There were 8.4% of patients lost to follow-up, even though acceptable in oncology [ 29 ] and rarely quantified in effectiveness studies [ 18 , 19 ]. Nonetheless, this population-based study included all patients registered at RON that were treated with the drug of interest in Portugal during the study period, an external validity advantage when compared to previous single-center retrospective cohort studies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%